Femmes enfermées du XIIe siècle: 'Aliénor, Héloïse et quelques autres' - Moulinier Brogi, Laurence (De Medio Aevo, 2020)
Thanks to an unprecedented experience, that of confinement on a global scale due to a pandemic, this article offers a reflection on the confinement of only a part of humanity, women, at a given time, the 12th century, as a modest contribution to the history of gender relations in the Middle Ages. Different women, in fact, underwent or on the contrary sought at that time isolation and seclusion: in all cases, their loneliness was linked to men, who inspired them to withdraw as a solution to escape marriage and sexuality, or required to get rid of their unwanted company. We therefore wonder here what are the faces and common points of the various forms of relegation that were going on, what resistance women could oppose, but also what were its limits: some of them chose the solitude as a pledge of peace and security but could they really be left alone? Could the recluses really provide for themselves? Were the imprisoned wives not kept in touch with the outside world, especially the male? At the end of this study, absolute solitude in the feminine seems more an ideal than a reality because even in the most austere cells, women could hardly do without men completely. On the other hand, confinement largely protected them physically, leaving in many cases other types of love than carnal one to flourish